2017
DOI: 10.5547/01956574.38.3.ebow
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Dependence in State Renewable Policy: Effects of Renewable Portfolio Standards on Renewable Generation within NERC Regions

Abstract: While several studies have examined the effect of renewable portfolio standard laws on renewable generation in states, previous literature has not assessed the potential for spatial dependence in these policies. Using recent spatial panel methods, this paper estimates a number of econometric models to examine the impact of RPS policies when spatial autocorrelation is taken into account. Consistent with previous literature, we find that RPS laws do not have a significant impact on renewable generation within a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…To account for the excess zeros in the count variable models, the zero-inflated Poisson was tested but was found to be only a weak improvement via the Vuong test (p = 0.07) (Vuong 1989), with very similar results to the classic Poisson. All models also include spatial fixed effects at the NERC (North American Electric Reliability Corporation) region level, following previous research documenting the effect of the RPS policy on renewable generation at the NERC region level (Bowen and Lacombe 2017). 13 The spatial fixed effects in our models account for policy spillovers and any other similarities in the electricity grid, solar potential, or consumer preferences within NERC regions.…”
Section: Data and Methods For Solar Capacity Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To account for the excess zeros in the count variable models, the zero-inflated Poisson was tested but was found to be only a weak improvement via the Vuong test (p = 0.07) (Vuong 1989), with very similar results to the classic Poisson. All models also include spatial fixed effects at the NERC (North American Electric Reliability Corporation) region level, following previous research documenting the effect of the RPS policy on renewable generation at the NERC region level (Bowen and Lacombe 2017). 13 The spatial fixed effects in our models account for policy spillovers and any other similarities in the electricity grid, solar potential, or consumer preferences within NERC regions.…”
Section: Data and Methods For Solar Capacity Modelsmentioning
confidence: 99%
“…All models also include spatial fixed effects at the NERC (North American Electric Reliability Corporation) region level, following previous research documenting the effect of the RPS policy on renewable generation at the NERC region level (Bowen and Lacombe 2017). The spatial fixed effects in our models account for policy spillovers and any other similarities in the electricity grid, solar potential, or consumer preferences within NERC regions.…”
Section: Empirical Analysismentioning
confidence: 99%
“…However, Shrimali and Kniefel (2011), Carley (2009), and Wiser et al (2007) have shown that the economic logic of the RPS mechanism and the associated PV deployment, REC and SREC prices is varied. The variation in impacts across states can be attributed to stringency of the percentage target, solar PV generation capacity required to meet the portfolio standard, and the types of RE technologies to be incentivized, such as solar PV, wind, fuel cells, geothermal, distributed generation, multipliers, small hydroelectric plants, and customer‐sited generation (Bowen & Lacombe, 2017). Variability of stringency in RPS targets poses difficulties in assessing the policy effectiveness of these economic instruments in promoting FFSPV diffusion and stable REC prices in the PJM markets.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…We regressed the FFSPV capacity on several covariates that we hypothesized to influence solar PV market. We modeled the overall vector of policy controls in the PJM market as follows: italicPJMitalicPOL=italicSRECsi,t1lnNEMi,t1ITCi,t1 Following Bowen and Lacombe (2017), we accounted for the optimal lag between the dependent variable, ShareitalicCapitalicititalicFFSPV, and other policy‐relevant utility choice variables in the PJM POL vector by calculating the natural logarithm of the policy variables between 𝑡 − 1 and 𝑡 − 3. To determine the optimal length of leads and lags required to correctly specify the potentially rich dynamics of PV and gas capacities, we followed Acemoglu et al (2019)'s practical approach which entails including only the lagged dependent variable alongside state and year fixed effects and adding lagged terms up to the point where the additional lag is not statistically significant.…”
Section: Estimation Approachmentioning
confidence: 99%
“…Aux Etats-Unis, l'impact sur la diffusion est clairement positif (Adelaja et al, 2010;Bowen and Lacombe, 2015;Delmas and Montes-Sancho, 2011;Krasko and Doris, 2013;Sarzynski et al, 2012) ou plus rarement non significatif (Shrimali et Jenner, 2013). Adelaja et al (2010); Menz et Vachon (2006) montrent ainsi un effet positif des politiques RPS sur la diffusion de l'énergie éolienne.…”
Section: Impact Des Politiques Basées Sur Des Quantités Sur La Diffusionunclassified